MLM dalam Persfektif Ulama' Fiqih dan Hadis - Khoirurroji'in, Lc., M.Pd.I (Jurnal At Taajir, 2020)
ABSTRACT Multi Level Marketing (MLM) better known as MLM is, "A direct sales system, where goods are marketed by consumers directly from producers. Consumers who simultaneously market goods receive bonus rewards. These bonuses are taken from the profits of each buyer introduced by first buyer based on regulated provisions "365. Because it is believed to be able to provide substantial profits to companies, today, various types of goods are widely marketed using MLM marketing patterns, jewelry. computer programs, supplement drinks, cosmetics, Islamic tapes and others. Transactions with this MLM system have penetrated the middle of humans and have a lot to color the atmosphere of the community market. So as a Muslim businessman, it is obligatory to know the legal transactions with this MLM system before struggling in it and the scholars have disagreed about the law. That a Muslim trader should know the Shari'a laws regarding the rules of trading or transactions and know the forms of buying and selling that are prohibited in religion. The lack of knowledge about this will cause a person to fall into error and sin. As we have witnessed the spread of usury practices, consuming human property in a vanity way, damaging market prices and so on from forms of damage that harm society, even harming the state. Keyword: Multi Level Marketing, MLM) Ulama Fiqih, Ulama Hadis, Perspektif